Mindfulness Training Alters Emotional Memory Recall Compared to Active Controls: Support for an Emotional Information Processing Model of Mindfulness - Roberts-Wolfe, Doug; Sacchet, Matthew; Hastings, Elizabeth; Roth, Harold; Britton, Willoughby (Frontiers in Human Neuroscience, 2012)
Objectives: While mindfulness-based interventions have received widespread application in both clinical and non-clinical populations, the mechanism by which mindfulness meditation improves well-being remains elusive. One possibility is that mindfulness training alters the processing of emotional information, similar to prevailing cognitive models of depression and anxiety. The aim of this study was to investigating the effects of mindfulness training on emotional information processing (i.e. memory) biases in relation to both clinical symptomatology and well-being in comparison to active control conditions. Methods: Fifty-eight university students (28 female, age = 20.1 ± 2.7 years) participated in either a 12-week course containing a "meditation laboratory" or an active control course with similar content or experiential practice laboratory format (music). Participants completed an emotional word recall task and self-report questionnaires of well-being and clinical symptoms before and after the 12-week course. Results: Meditators showed greater increases in positive word recall compared to controls F(1, 56) = 6.6, p = .02). The meditation group increased significantly more on measures of well-being [F(1, 56) = 6.6, p = .01], with a marginal decrease in depression and anxiety [(F(1, 56) = 3.0, p = .09)] compared to controls. Increased positive word recall was associated with increased psychological well-being [r = 0.31, p = .02] and decreased clinical symptoms [r = -0.29, p = .03]. Conclusion: Mindfulness training was associated with greater improvements in processing efficiency for positively valenced stimuli than active control conditions. This change in emotional information processing was associated with improvements in psychological well-being and less depression and anxiety. These data suggest that mindfulness training may improve well-being via changes in emotional information processing.